2021
DOI: 10.1016/j.isci.2021.103066
|View full text |Cite
|
Sign up to set email alerts
|

Chemogenetic activation of nigrostriatal dopamine neurons in freely moving common marmosets

Abstract: To interrogate particular neuronal pathways in nonhuman primates under natural and stress-free conditions, we applied designer receptors exclusively activated by designer drugs (DREADDs) technology to common marmosets. We injected adeno-associated virus vectors expressing the excitatory DREADD hM3Dq into the unilateral substantia nigra (SN) in four marmosets. Using multi-tracer positron emission tomography imaging, we detected DREADD expression in vivo, which was confirmed in nigrostriatal dopamine neurons by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 53 publications
3
28
0
Order By: Relevance
“…Thus, 3-30 μg/kg would be an effective range for activating hM3Dq via oral administration. Indeed, we have recently demonstrated that marmosets expressing hM3Dq produced consistent behavioral changes when fed a diet containing 10 μg/kg of DCZ ( Mimura et al, 2021 ). In any case, it should be noted that the optimal agonist dose generally depends on the level of the overexpressed functional protein ( Upright et al, 2018 ) and the targeted circuit to be manipulated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, 3-30 μg/kg would be an effective range for activating hM3Dq via oral administration. Indeed, we have recently demonstrated that marmosets expressing hM3Dq produced consistent behavioral changes when fed a diet containing 10 μg/kg of DCZ ( Mimura et al, 2021 ). In any case, it should be noted that the optimal agonist dose generally depends on the level of the overexpressed functional protein ( Upright et al, 2018 ) and the targeted circuit to be manipulated.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, its superior efficacy and brain permeability permit its use for oral administration. Indeed, it has been demonstrated that orally delivered DCZ effectively induces behavioral changes in mice and marmosets ( Krause et al, 2021 ; Mimura et al, 2021 ). However, the long-term chemogenetic action of DCZ remains unclear, specifically in terms of the duration of a single-dosage effect and the impact of repetitive doses over several days to weeks.…”
Section: Introductionmentioning
confidence: 99%
“…The number of applications of chemogenetics to non-human primates is smaller than that of optogenetics, with only a dozen cases ( Eldridge et al, 2016 ; Grayson et al, 2016 ; Nagai et al, 2016 , 2020 ; Upright et al, 2018 ; Raper et al, 2019 ; Hayashi et al, 2020 ; Deffains et al, 2021 ; Hirabayashi et al, 2021 ; Mimura et al, 2021 ; Oguchi et al, 2021b ; Oyama et al, 2021 , 2022 ; Allen et al, 2021 ; Jeurissen et al, 2022 ). These included studies that examined the effects of local interventions on widespread neural networks by fMRI to observe whole-brain network changes, while locally expressing DREADDs and systematically administering the ligand.…”
Section: Pathway-selective Manipulation Of the Macaque Prefrontal Net...mentioning
confidence: 99%
“…In addition, the delineation of the internal and external globus pallidus can aid in the MRI-guided targeting of the inhibitory and excitatory output of the cortico-striatal-thalamic circuit during micro-stimulation. The identification and visualization of small subcortical structures are likewise beneficial for neuroscientists implementing optogenetic (Galvan et al, 2017;Inoue et al, 2015) or chemogenetic interventions (Mimura et al, 2021). Hence, the correct delineation of the subcortical deep gray matter nuclei, while maintaining adequate anatomical information of the whole brain, is crucial for precise interventional studies and clinical applications.…”
Section: Dadarwal Et Al 2021mentioning
confidence: 99%
“…In addition, the delineation of the internal and external globus pallidus can aid in the MRI-guided targeting of the inhibitory and excitatory output of the cortico-striatal-thalamic circuit during micro-stimulation. The identification and visualization of small structures are likewise beneficial for neuroscientists implementing optogenetic (Galvan et al, 2017;Inoue et al, 2015) or chemogenetic interventions targeting deep brain nuclei (Mimura et al, 2021).…”
Section: Quantitative Susceptibility Mapping Of the Nonhuman Primate ...mentioning
confidence: 99%